Excess prevalence of chronic diseases in elderly people with diabetes and non-diabetics in Poland - Katarzyna Więckiel-Lisowska; Agata Wojciechowska; Łukasz Wierucki; Sonia Woch; Krzysztof Flis; Adrian Lange; Marcin Rutkowski; Tomasz Zdrojewski; Piotr Bandosz (PLoS ONE, 2025)
Objective Diabetes increases the risk of several chronic conditions. However, their excessive prevalence among older adults with diabetes in Poland is unknown. Methods The prevalence of chronic diseases was assessed in the nationally representative random sample of 5,987 Polish adults aged 60+ (Polsenior2 study, data collected between 2018 and 2020). Each participant’s history of hospitalisation due to coronary heart disease (CHD), stroke, and cancer was assessed. Diagnosis of arterial hypertension (AH), cognitive impairment (CI), and chronic kidney disease (CKD) was established based on the questionnaire, blood pressure measurements, Mini-Mental State Examination, and laboratory tests. Diabetes was diagnosed if the participant reported being diagnosed with the disease or their measured HbA1c was ≥ 48 mmol/mol (≥6.5%). Age- and sex-adjusted prevalence ratios of chronic conditions for participants with diabetes versus those without diabetes were calculated using Poisson regression. Results In the multivariate model, the prevalence ratio for CHD history was 1.98 (95%CI: 1.66–2.37), for CKD: 1.90 (95%CI: 1.66–2.18), for stroke: 1.47 (95%CI: 1.15–1.88), for AH: 1.22 (95%CI: 1.17–1.27). Cancer and cognitive impairment prevalence did not differ between people with and without diabetes. The mean number of chronic diseases was 52% higher in participants with diabetes vs nondiabetic subjects at age 60–69 (1.72 (95%CI: 1.60–1.84) vs. 1.13 (95%CI: 1.07–1.18), respectively). However, this value was only 10% higher in subjects aged 90+ (2.74 (95%CI: 2.45–3.04) vs. 2.49 (95%CI: 2.37–2.62), respectively). Conclusions Elderly Polish citizens with diabetes suffer more often from coronary heart disease, stroke, chronic kidney disease, and arterial hypertension. The study emphasises that the excess prevalence of chronic diseases among people with diabetes is high in the youngest-old population but diminishes in the oldest-old people.